2011
DOI: 10.1128/mbio.00239-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing Reveals a Phage in Helicobacter pylori

Abstract: Helicobacter pylori chronically infects the gastric mucosa in more than half of the human population; in a subset of this population, its presence is associated with development of severe disease, such as gastric cancer. Genomic analysis of several strains has revealed an extensive H. pylori pan-genome, likely to grow as more genomes are sampled. Here we describe the draft genome sequence (63 contigs; 26× mean coverage) of H. pylori strain B45, isolated from a patient with gastric mucosa-associated lymphoid ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 71 publications
3
93
0
5
Order By: Relevance
“…The titer of the progeny phage reached 10 9 PFU/ml after several rounds of amplification using fresh cultures of strain NCTC 11637 with the supernatants from a previous lysate. This differs from the case of phage HP33, which was difficult to amplify (29). During storage, the 1961P phage in crude lysates was stable at 4°C, and no significant loss in infectivity was found after 3 months, as determined by monitoring at intervals of 10 days.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The titer of the progeny phage reached 10 9 PFU/ml after several rounds of amplification using fresh cultures of strain NCTC 11637 with the supernatants from a previous lysate. This differs from the case of phage HP33, which was difficult to amplify (29). During storage, the 1961P phage in crude lysates was stable at 4°C, and no significant loss in infectivity was found after 3 months, as determined by monitoring at intervals of 10 days.…”
Section: Resultsmentioning
confidence: 98%
“…Vale et al (46) described the release of phage-like particles by H. pylori following UV induction. Lehours et al (29) discovered that temperate phage of the Siphoviridae family was released from H. pylori strain B45 following induction. Wan et al (49) isolated a virulent phage of H. pylori.…”
mentioning
confidence: 99%
“…Several bacteriophages (phages) of H. pylori have been reported (4,5,9,12). In general, phages are considered to contribute to bacterial evolution and may affect host features, such as biological behavior, pathogenesis, or adaptation, via their possible roles in horizontal gene transfer and bacteria-phage antagonistic coevolution (4,5,7).…”
mentioning
confidence: 99%
“…In general, phages are considered to contribute to bacterial evolution and may affect host features, such as biological behavior, pathogenesis, or adaptation, via their possible roles in horizontal gene transfer and bacteria-phage antagonistic coevolution (4,5,7). In this study, to extend our understanding not only of the H. pylori phages themselves but also of the process of coevolution of H. pylori and its phages, phages KHP30 and KHP40 were isolated from the culture supernatants of East Asian-type isolates from Japanese patients living in distinct geographic regions, and their complete genomic sequences were determined.…”
mentioning
confidence: 99%
“…This diversity can be attributed to altered DNA repair, elevated mutation rates, high frequency of intraspecific recombination, chromosomal DNA transfer events from other species, incorporation of naked DNA from the environment, plasmid mobilization, and integration of acquired DNA in the so-called plasticity zones [4,[8][9][10]. In addition, the presence of phages has been described for several H. pylori strains, acting as another source of bacterial diversity and evolution [11][12][13][14][15]. Using newly developed bioinformatics programs, recent comparative studies of 29 complete genome sequences of strains from different parts of the world revealed a high-resolution picture of the H. pylori population structure as well as the extent and direction of genetic flux between subgroups of the bacterium [16].…”
Section: Introductionmentioning
confidence: 99%